The characterization of purified recombinant protein CRM197 as a tool to study diphtheria toxin - Manoilov, K. Yu.; Gorbatiuk, O. B.; Usenko, M. O.; Shatursky, O. Ya.; Borisova, T. A.; Kolibo, D. V. (Reports of the National Academy of Sciences of Ukraine, 2016)
The purification of non-toxic diphtheria toxoid CRM197 expressed in Esherichia coli by metal-affinity chromatography following the enzymatic digestion of a bacterial cell wall and DNA allowed us to avoid the contamination by endogenous pore-forming proteins. It was shown that the fluorescein isothiocyanate-labeled samples of CRM197 are capable of binding and internalizing by mammalian cells Vero and L929. The introduction of CRM197 (2–20 nM) at positive voltages from the side of phosphatidylethanolamine-containing bilayer membrane (BLM ), were the toxoid was added, resulted in the creation of potential-dependent ionic channels with the conductance of 20 pS in the bathing solution of 1M KCl buffered at pH 4.8, as had been shown in classic studies of wild-type diphtheria toxin. The activation energies measured for the CRM197-created steady-state macroscopic current on one side of BLM in the solution of 1M KCl (pH 6.0) and the solution without membrane are equal to 2.967 ± 0.167 kcal/mol and 2.933 ± 0.115 kcal/mol, respectively, which suggests the formation of a transmembrane water pore by CRM197.